Evaluation Program of Work Practice in Industrial Vocational High School (Seen From Respondents Teacher Supervisor) - Yumn Jamilah; Sukardi Sukardi; Elfi Tasrif; Fadly Nendra; Elsa Firdianis (International Journal of Educational Dynamics, 2020)
This study aimed to describe the context, input, process, product industry work practices program at SMK Negeri 1 Lintau. This research is CIPP evaluation model. The methodology used is the method of combination (Mixed Methods) design verification sequence (Sequential Explanatory). The research was conducted at SMK Negeri 1 Lintau. The informants are the principal, chairman prakerin, tutor, mentor and student industry. The technique of collecting data through observation, questionnaires, and interviews. Based on data analysis found that the level of achievement prakerin program from the aspects of respondents Teacher Advisor to the variable context prakerin program at SMK Negeri 1 Lintau amounted to 83.77% in both categories. Input variables prakerin program at SMK Negeri 1 Lintau for 82,23% in both categories. Variable process prakerin program at SMK Negeri 1 Lintau amounted to 79.40% with enough.Variabel product category prakerin program at SMK Negeri 1 Lintau amounted to 80.75%.